Long-term trends in urban NO2 concentrations and associated paediatric asthma incidence: estimates from global datasets. Issue 1 (January 2022) - Anenberg, Susan C; Mohegh, Arash; Goldberg, Daniel L; Kerr, Gaige H; Brauer, Michael; Burkart, Katrin; Hystad, Perry; Larkin, Andrew; Wozniak, Sarah; Lamsal, Lok
Summary: Background: Combustion-related nitrogen dioxide (NO2 ) air pollution is associated with paediatric asthma incidence. We aimed to estimate global surface NO2 concentrations consistent with the Global Burden of Disease study for 1990–2019 at a 1 km resolution, and the concentrations and attributable paediatric asthma incidence trends in 13 189 cities from 2000 to 2019. Methods: We scaled an existing annual average NO2 concentration dataset for 2010–12 from a land use regression model (based on 5220 NO2 monitors in 58 countries and land use variables) to other years using NO2 column densities from satellite and reanalysis datasets. We applied these concentrations in an epidemiologically derived concentration–response function with population and baseline asthma rates to estimate NO2 -attributable paediatric asthma incidence. Findings: We estimated that 1·85 million (95% uncertainty interval [UI] 0·93–2·80 million) new paediatric asthma cases were attributable to NO2 globally in 2019, two thirds of which occurred in urban areas (1·22 million cases; 95% UI 0·60–1·8 million). The proportion of paediatric asthma incidence that is attributable to NO2 in urban areas declined from 19·8% (1·22 million attributable cases of 6·14 million total cases) in 2000 to 16·0% (1·24 million attributable cases of 7·73 million total cases) in 2019. Urban attributable fractions dropped in high-income countries (–41%), Latin America and the Caribbean (–16%), central Europe, eastern Europe, and central Asia (–13%), and southeast Asia, east Asia, and Oceania (–6%), and rose in south Asia (+23%), sub-Saharan Africa (+11%), and north Africa and the Middle East (+5%). The contribution of NO2 concentrations, paediatric population size, and asthma incidence rates to the change in NO2 -attributable paediatric asthma incidence differed regionally. Interpretation: Despite improvements in some regions, combustion-related NO2 pollution continues to be an important contributor to paediatric asthma incidence globally, particularly in cities. Mitigating air pollution should be a crucial element of public health strategies for children. Funding: Health Effects Institute, NASA.